Hypoxia compensates cell cycle arrest with progenitor differentiation during angiogenesis. Issue 5 (29th March 2020) - Acosta‐Iborra, Bárbara; Tiana, Maria; Maeso‐Alonso, Laura; Hernández‐Sierra, Rosana; Herranz, Gonzalo; Santamaria, Andrea; Rey, Carlos; Luna, Raquel; Puente‐Santamaria, Laura; Marques, Margarita M.; Marin, Maria C.; del Peso, Luis; et al.
Abstract: Angiogenesis, the main mechanism that allows vascular expansion for tissue regeneration or disease progression, is often triggered by an imbalance between oxygen consumption and demand. Here, by analyzing changes in the transcriptomic profile of endothelial cells (ECs) under hypoxia we uncovered that the repression of cell cycle entry and DNA replication stand as central responses in the early adaptation of ECs to low oxygen tension. Accordingly, hypoxia imposed a restriction in S‐phase in ECs that is mediated by Hypoxia‐Inducible Factors. Our results indicate that the induction of angiogenesis by hypoxia in Embryoid Bodies generated from murine Stem Cells is accomplished by the compensation of decreased S‐phase entry in mature ECs and differentiation of progenitor cells. This conditioning most likely allows an optimum remodeling of the vascular network. Identification of the molecular underpinnings of cell cycle arrest by hypoxia would be relevant for the design of improved strategies aimed to suppress angiogenesis in pathological contexts where hypoxia is a driver of neovascularization.